Effectiveness of a 5-Week Virtual Reality Telerehabilitation Program for Children With Duchenne and Becker Muscular Dystrophy: Prospective Quasi-Experimental Study - María Rosa Baeza-Barragán; Maria Teresa Labajos Manzanares; Mercedes Cristina Amaya-Álvarez; Fabián Morales Vega; Judit Rodriguez Ruiz; Rocío Martín-Valero (JMIR Publications, 2023)
Abstract BackgroundDuchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are neuromuscular diseases. DMD is the most prevalent in children. It affects dystrophin production, reducing the patient's mobility and quality of life. New technologies have become a part of physical therapy in DMD and BMD. During the COVID-19 pandemic, conducting telerehabilitation through virtual reality-based games could help these children maintain their physical abilities. ObjectiveThis study examined if the use of a virtual platform in a multimodal intervention program changes the results of the 6-minute walk test (6MWT) in children with DMD and BMD. The main objective was to test whether children with DMD and BMD obtain different results on the 6MWT after completing 10 telerehabilitation treatment sessions. The secondary objective was to measure whether other specific motor scales also produce different results after the 10 defined sessions. MethodsThis was a descriptive, open, and quasi-experimental study with a prospective A-B (control-intervention) design. A sample of 12 participants who fulfilled the inclusion criteria followed the program for 5 weeks with 10 telerehabilitation sessions. During the sessions, the participants used virtual reality glasses to train for the treatment goals. All participants were assessed in person before and after the intervention. Analysis was performed using R software according to the different functional assessments performed for each test. ResultsThe participants showed a 19.55-meter increase in the 6MWT. Motor function also remained stable according to other scales used to assess it. The North Start Ambulatory Assessment scores were stable in both treatment conditions (PP ConclusionsThere were no differences between conventional and telerehabilitation treatments, so the telerehabilitation tool could be used without harming children with DMD and BMD, facilitating their access to therapies and stimulating learning to maintain their functional capacity. Therefore, telerehabilitation in general may be helpful in maintaining motor function in children with DMD and BMD. The learning effect helped reduce the feeling of fatigue in the children during the program.